Fostering a Learning Ethic Through Vocational Training for Fostered Youth - Salsabiil Ronnaan; Nayla Nanda Friadi; Sabda Nabil; Rika Fitri Ramadani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article discusses the development of a learning ethos among at-risk youth through vocational training programs, specifically in welding and automotive repair. This article is based on data from program evaluations obtained through observation and interviews. The study's findings indicate that participants' learning ethos is shaped through a practice-based learning approach (learning by doing), which encourages active participation, discipline, and responsibility in completing tasks. Additionally, the role of instructors, a structured learning environment, and the relevance of the material to workplace needs further strengthen participants' learning ethos. The impact of a strong learning ethos is evident in the improvement of technical skills, self-confidence, and the participants' ability to apply these skills for employment or entrepreneurship. However, further strengthening is needed in the areas of workplace safety and mentoring tailored to the participants' capabilities. Thus, the learning ethos becomes a critical factor in the success of training and empowerment programs for youth under supervision